Determination of Physical and Cooking Properties of Bamboo Rice - , Shruthi. K. J, M. L. Revanna, K. G. Vijayalaxmi, Shamshad Begum (Archives of Current Research International, 2025)
The preference, choice and the economy of rice largely depends on its physical and cooking properties. 5 parameters of physical properties and 7 parameters of cooking properties were evaluated based on the standard protocols. The results showed that length and breadth were highest for white rice (6.63 mm and 3.00 mm respectively) than Bamboo rice (6.58 mm and 2.38 mm respectively). Whereas L/B ratio, 1000 kernel weight and bulk density were highest for Bamboo rice (2.76, 13.68 g and 1.65 g/ml respectively) than white rice (2.21, 10.24 g and 1.62 g/ml respectively). Cooking parameters results showed that Alkali spreading value, gel consistency and dispersed solids were highest for white rice (3.0, 55.33 and 6.33% respectively) than bamboo rice (2.0, 49.80 and 4.64% respectively) whereas, gelatinization temperature, minimum cooking time, optimum cooking time and water uptake ratio were found to be highest for bamboo rice (71.66oC, 56.80 min, 58.75 min and 4.48 respectively) than white rice (70.09oC, 13.50 min, 15.80 min and 2.68 respectively). The information on physical and cooking properties of bamboo rice can be exploited by nutritionists and utilized for practical applications in food technology.